A kind of steel for bolts and its production method and heat treatment method

By optimizing the chemical composition and smelting process in bolt steel, a pearlite + ferrite + a small amount of bainite is formed, and through quenching and tempering treatment, the problem of difficult to take into account both the corrosiveness and strength of bolts in the marine environment is solved. , achieves the effects of high corrosion resistance and high fatigue life, while reducing costs.

CN116288056BActive Publication Date: 2025-01-10МААНЬШАНЬ АЙРОН ЭНД СТИЛ КО ЛТД
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310231116.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-13
Publication Date
2025-01-10
Estimated Expiration
2043-03-13

AI Technical Summary

Technical Problem

In marine environments, existing bolts are difficult to meet due to corrosive materials and high strength requirements, and the addition of precious metal elements increases costs, and corrosion resistance and toughness are difficult to take into account.

Method used

Chemical components are C 0.40% to 0.50%, Si 1.10% to 1.30%, Mn 0.40% to 0.60%, Mo 0.35% to 0.45%, Cr 0.80% to 1.00%, Ni 0.60% to 0.80%, Tb 0.0050% to 0.0080% of the steel for bolts, through specific smelting and heat treatment processes, a pearlite + ferrite + a small amount of bainite is formed, and the inclusion size is controlled below 8.0μm. Quenching and tempering are used to improve strength and resistance. Corrosive.

Benefits of technology

The high strength, delayed fracture resistance and high fatigue life of the bolt are achieved, and the corrosion resistance in marine environment is more than three times that of the market-general high-strength bolts, and the alloy cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116288056B_ABST
    Figure CN116288056B_ABST
Patent Text Reader

Abstract

The present invention discloses a bolt steel and a production method and a heat treatment method thereof. The bolt steel contains C, Si, Mn, Alt, Mo, Cr, Ni and Tb elements, wherein the Cl-resistant ‑ The corrosion index C value is ≥7.39, the purity index A value is ≥1.25, the structure of the bolt steel is pearlite + ferrite + a small amount of bainite, the bainite content is controlled at 10%, the inclusions in the steel are all plastic inclusions, and the size is below 8.0μm. After heat treatment, the mechanical properties of the bolt steel can reach 13.9 and 14.9, and it has excellent delayed fracture resistance and high room temperature impact toughness and low temperature impact toughness. The corrosion resistance in the marine environment can reach more than 3 times that of the high-strength bolt steel commonly used in the market, and it has low notch sensitivity, high delayed fracture resistance and high fatigue life, and is suitable for making ultra-high strength bolts used in marine environments and other harsh open-air environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cold heading steel, and in particular relates to a steel for bolts and a production method and a heat treatment method thereof. Background Art

[0002] Bolts are mainly produced by cold heading steel. Various equipment in the marine environment are connected by bolts, but due to the complex application environment and long-term corrosion by seawater, ordinary bolts will suffer serious corrosion. In addition, the marine environment must withstand various climatic conditions and waves, suffer from seawater corrosion, and the working environment conditions are very harsh. In addition, the development area is developing from warm sea areas to low-temperature cold sea areas, which requires steel with high room temperature impact toughness and low temperature impact toughness.

[0003] Chinese patent CN101397634B discloses atmospheric corrosion resistant 08CrNiCu low alloy high strength annealing-free cold heading steel and production process, characterized in that the chemical composition ratio is C: 0.05-0.90%, Si: 0.15-0.25%, Mn: 0.55-0.65%, P: 0.005-0.025%, S: 0.005-0.02%, Cr: 0.65-0.75%, Ni: 0.25-0.30%, Cu: 0.35-0.40%, and the rest is Fe and unavoidable impurities; it can be used to process 8.8 grade bolts and matching nuts. The disadvantage is that the steel of the invention adds precious alloy elements such as Ni and Cr, and the cost is relatively high.

[0004] Chinese patent CN108070796A discloses a delayed fracture 1040MPa grade corrosion-resistant bolt, the mass percentage of which chemical composition is: C: 0.21-0.32, Si: 0.10-0.50, Mn: 0.60-1.00, P: 0.008-0.020, S: ≤0.005, Cr: 0.82-1.20, Ni: 0.25-0.50, Cu: 0.25-0.50, Mo: 0.05-0.20, Nb: 0.015-0 .060, V: 0.015-0.090, Ti: 0.008-0.035, B: 0.0008-0.0035, Al: 0.015-0.040, Ca: 0.003-0.007, Zr: 0.015-0.045, Re: 0.010-0.045, the balance is Fe and unavoidable impurities; the preparation method of the above bolts mainly adopts conventional high-purity smelting-continuous casting-rolling technology, and the bolts produced are both resistant to delayed fracture and atmospheric corrosion. However, the addition of Ti and Zr elements in this method will form nitride inclusions, which is harmful to the toughness of the material.

[0005] At present, there are many studies on corrosion-resistant construction steels such as plates and steel sections in my country, and the products are relatively mature, but there are few studies on corrosion-resistant cold heading steels. With the complexity of the application environment of fasteners, it is urgent to develop fastener steel materials with corrosion resistance. Summary of the invention

[0006] The object of the present invention is to provide a steel for bolts and a production method thereof, wherein the structure of the steel for bolts is pearlite + ferrite + a small amount of bainite, the bainite content is controlled at 10%, the inclusions in the steel are all plastic inclusions, the size is below 8.0 μm, the oxide inclusions K0 (O) ≤ 2, and one-third of the cold heading is qualified.

[0007] Another object of the present invention is to provide a heat treatment method for bolt steel. After heat treatment, the mechanical properties of the bolt steel can reach level 13.9 and level 14.9, and it has excellent delayed fracture resistance, high room temperature impact toughness, and low temperature impact toughness. The corrosion resistance in the marine environment can be more than three times that of the high-strength bolt steel commonly used in the market. It also has low notch sensitivity, high delayed fracture resistance and high fatigue life, and is suitable for the production of ultra-high strength bolts for use in marine environments and other harsh open-air environments.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] The invention provides a bolt steel, which contains, by weight percentage, C 0.40%-0.50%, Si 1.10%-1.30%, Mn 0.40%-0.60%, Alt 0.020%-0.030%, Mo 0.35%-0.45%, Cr 0.80%-1.00%, Ni 0.60%-0.80%, Tb 0.0050%-0.0080%, P≤0.015%, S≤0.015%, Cu≤0.10%, O≤0.0015%, H≤0.0002%, and the rest is Fe and other inevitable impurities;

[0010] In order to ensure that the steel has sufficient corrosion resistance, the chemical composition ratio must ensure Cl resistance - Corrosion index C value ≥ 7.38,

[0011] C=1.55(%Si)+3.97(%Ni)+1.85(%Cr)+2.03(%Mo)+6.42(%P)-7.23(%Ni)(%P)+69.72(%Tb);

[0012] In order to ensure that the steel of the present invention has a high purity, all plastic inclusions are below 8.0 μm in size, and it is necessary to ensure that the A value is ≥ 1.25, A = (% Tb) / ((% S) + (% O)).

[0013] The metallographic structure of the bolt steel is pearlite+ferrite+a small amount of bainite, and the volume percentage of bainite is controlled below 10%.

[0014] The bolt steel is quenched at 890-910°C and then oil-cooled, and then tempered at 570°C±20°C and then air-cooled. Its mechanical properties reach level 13.9, with Rm≥1300MPa, Rp0.2≥1170MPa, A≥8%, Z≥44%, and yield strength ratio≥0.9.

[0015] The bolt steel is quenched at 900°C±10°C and then oil-cooled, and then tempered at 530°C±20°C and then air-cooled. Its mechanical properties reach level 14.9, with Rm≥1400MPa, Rp0.2≥1260MPa, A≥8%, Z≥43%, and yield strength ratio≥0.9.

[0016] After quenching and tempering, the bolt steel has a KV2 impact toughness value of ≥200J at room temperature of 25°C, a KV2 impact toughness value of ≥90J at low temperature of -90°C, a relative corrosion rate of ≤33% in a 3.5%wt NaCl solution immersion test, a notch sensitivity NSR value of ≥1.65, a delayed fracture strength ratio of ≥0.80, and an axial fatigue cycle number of >2 million times under a load of 200KN.

[0017] The present invention also provides a production method for the bolt steel, which comprises the following steps: molten iron pretreatment → electric furnace or converter smelting → LF furnace refining → RH refining → billet continuous casting → billet heating → high-speed wire rolling → Stelmor cooling line cooling → Φ5.5-50mm wire rod finished product.

[0018] The electric furnace or converter smelting: the electric furnace or converter end point C≤0.04%, P≤0.006%; slag blocking for tapping, strict control of slag amount, slag layer thickness of the ladle≤100mm, tapping time≥5min.

[0019] The LF furnace refining: LF refining time is ≥30min, and white slag holding time is ≥20min, so as to ensure sufficient deoxidation, desulfurization and dephosphorization.

[0020] In the RH refining step, the RH vacuum control time is ≥20 minutes, and Tb blocks are added 10 minutes to 12 minutes before breaking the vacuum. If Tb is added earlier than this time, it is easy to be over-oxidized, resulting in a low yield. If it is added later than this time, the Tb element cannot fully react in the molten steel, resulting in insufficient plasticization of inclusions.

[0021] In the billet heating step, the soaking temperature of the heating furnace is controlled at 950° C. to 1000° C. Above this temperature, decarburization and coarsening of grains are likely to occur on the billet surface, while below this temperature, alloy elements cannot be fully dissolved in austenite.

[0022] In the high-speed wire rolling step, a controlled rolling and controlled cold rolling process is adopted, and the wire drawing temperature is controlled at 830°C to 860°C. Below this temperature, the steel is prone to undergo martensitic phase transformation before entering the cooling line. Above this temperature, the entire phase transformation cannot be completed on the cooling bed, and abnormal martensite is then produced at the reel position. In the cooling step of the Stelmor cooling line, the Stelmor wire insulation cover is fully closed, and the cooling rate is controlled below 0.13°C / s to ensure sufficient pearlite phase transformation, and finally a structure of pearlite + ferrite + a small amount of bainite is obtained, and the bainite content is controlled below 10%. This structure has good processing properties and is beneficial to user drawing.

[0023] The heat treatment method comprises the following steps: first quenching at 900℃±10℃ and then oil cooling, then tempering at 570℃±20℃ and then air cooling; or, first quenching at 900℃±10℃ and then oil cooling, then tempering at 530℃±20℃ and then air cooling. After quenching and tempering heat treatment, the strength of the steel can reach 13.9 to 14.9, and it has excellent delayed fracture resistance and high room temperature impact toughness and low temperature impact toughness. The corrosion resistance in the marine environment can reach more than 3 times that of the high-strength bolt steel commonly used in the market, and it has low notch sensitivity, high delayed fracture resistance and high fatigue life, and is suitable for making ultra-high strength bolts used in marine environments and other harsh open-air environments.

[0024] In the bolt steel provided by the present invention, the functions and controls of the various components are as follows:

[0025] C: C is the most basic and effective strengthening element in steel, but as its content increases, ductility decreases. The C content is controlled at 0.40% to 0.50%.

[0026] Si: Si is concentrated on the surface of corrosion-resistant steel and can significantly increase the - The resistance of the rust layer and the charge transfer resistance in the environment are improved, the stability of the rust layer is improved, and the corrosion resistance is improved. In addition, in ultra-high strength steel, Si significantly improves the elastic limit, yield strength and yield strength ratio of the steel, and improves fatigue strength. However, the increase of Si element will increase the diffusion of carbon in the steel and aggravate the decarburization of the steel. The Si content is controlled at 1.10% to 1.30%.

[0027] Mn: Mn and Fe form a solid solution to improve the hardness and strength of ferrite and austenite in steel, but excessive Mn will reduce the plasticity and yield strength of steel, and will also cause the growth of corrosion product particles and increase the corrosion rate. The Mn content is controlled at 0.40% to 0.60%.

[0028] Mo: The main role of Mo in steel is to improve hardenability, tempering resistance and prevent tempering brittleness. In addition, the reasonable combination of Mo and Cr can significantly improve hardenability and tempering resistance. Mo carbides are relatively small, forming dense "hydrogen traps" in steel, improving delayed fracture resistance. In addition, Mo can also improve the pitting and crevice corrosion resistance of steel. If the Mo content is too low, the above effects are limited. If the Mo content is too high, the above effects are saturated and the cost of steel is increased. Therefore, the Mo content is controlled to be 0.35% to 0.45%.

[0029] Cr: Cr element significantly improves toughness and strength in steel. Cr can form a dense oxide film on the surface of steel, improve the passivation ability of steel, and improve the weather resistance of steel. However, excessive Cr increases the brittleness tendency of steel. The Cr content is controlled at 0.80% to 1.00%.

[0030] Ni: Ni can form an infinitely miscible solid solution with Fe, which has the effect of expanding the phase region and does not form carbides. Ni can stabilize austenite and enhance the hardenability of steel. Ni is also an effective element for reducing the ductile-brittle transition temperature and significantly improves low-temperature toughness. Ni exists in the rust layer in the form of NiFe2O4. Compared with Fe3O4, NiFe2O4 has higher thermodynamic and electrochemical stability, which makes the rust layer more stable, thus helping to reduce the corrosion rate.

[0031] Tb: Tb is also a key element of the steel of the present invention. Large-sized inclusions in the steel become defect points, which will reduce the toughness, plasticity and service life of the steel. In the corrosion-resistant steel, pitting corrosion is also likely to occur, accelerating the corrosion rate. The steel of the present invention adds Tb to modify the inclusions in the steel, reacting with oxygen and sulfur in the steel to generate high-melting-point spherical rare earth sulfides and rare earth oxysulfides randomly distributed in the crystal, replacing the more harmful Al2O3 inclusions and sulfide inclusions in the experimental steel, while promoting the dispersion of fine spherical inclusions and improving the purity of the molten steel. The steel of the present invention also controls the A value ≥ 1.25, A = (% Tb) / ((% S) + (% O)), to ensure that all inclusions are fully plasticized and the size is below 8.0 μm, thereby improving the comprehensive performance of the steel and the service life of the bolts.

[0032] In addition, Tb is enriched in the rust layer of steel, which accelerates the cathode reduction of the rust layer, inhibits the dissolution of the anode, and can significantly improve its corrosion resistance. The steel of the present invention reduces the content of precious metals Ni and Cu in traditional Cr-Ni-Cu corrosion-resistant steel by adding Tb elements, effectively saving alloy costs. In order to achieve a corrosion resistance of more than three times that of the 12.9 grade bolt steel commonly used in the market, the chemical composition ratio must ensure that the corrosion resistance index C value is ≥7.38, C = 1.55 (% Si) + 3.97 (% Ni) + 1.85 (% Cr) + 2.03 (% Mo) + 6.42 (% P) - 7.23 (% Ni) (% P)+69.72(%Tb), through the composite action of various corrosion-resistant elements, they precipitate at the interface between the rust layer and the substrate, forming a barrier layer firmly combined with the substrate, blocking the further dissolution of the substrate and promoting the formation of an amorphous FeOOH protective film. α-FeOOH is the most stable phase in the rust layer. Basically, no phase evolution occurs in the rust layer, and no defects such as cracks or holes are caused in the rust layer due to volume change caused by phase evolution. If the value is lower than this, the corrosion resistance of the steel of the present invention cannot be achieved.

[0033] Cu: Cu will increase the brittleness and crack sensitivity. It is not added in the steel of the present invention because the ultra-high strength bolts have a high risk of delayed fracture due to their high strength. In addition, high-strength bolts are notch-sensitive parts due to thread rolling. If Cu is added, the risk of fracture will be further increased due to increased brittleness and crack sensitivity. Control Cu ≤ 0.10%.

[0034] S and P: Sulfur easily forms MnS inclusions with manganese in steel, which is harmful to the processing properties of steel; P is an effective corrosion-resistant element, but it is not suitable to be added to bolt steel because P is an element with a strong segregation tendency, which will cause cold brittleness and lead to cold heading cracking. Control P≤0.015%, S≤0.015%.

[0035] O: O forms oxide inclusions in steel, which damages the processing performance and service life of the steel. Control O≤0.0015%.

[0036] H: When the strength of steel exceeds 1200MPa, the risk of hydrogen-induced delayed fracture increases significantly. Therefore, various measures are taken to reduce the H content as much as possible and control H≤0.0002%.

[0037] The bolt steel provided by the present invention is characterized by the content of each component, resistance to Cl - Precise control of the corrosion index C value and A value has resulted in bolt steel with corrosion resistance, high strength and toughness, and long life. The inclusions in the bolt steel are all plastic inclusions with a size of less than 8.0 μm, oxide inclusions K0(O)≤2, and one-third of the cold heading is qualified.

[0038] In the production method of bolt steel provided by the present invention, a process route of molten iron pretreatment → electric furnace or converter smelting → LF furnace refining → RH refining → billet continuous casting → billet heating → high-speed wire rolling → Stelmor cooling line cooling → Φ5.5-50mm wire rod finished product is adopted to produce bolt steel with a metallographic structure of pearlite + ferrite + a small amount of bainite, and the bainite content is controlled below 10%. After the bolt steel is subjected to quenching and tempering heat treatment, the strength of the steel can reach 13.9-14.9, the KV2 impact toughness value at 25°C room temperature is ≥200J, and the KV2 impact toughness value at -90°C low temperature is ≥90J. Compared with the commonly used 12.9 grade high-strength bolt steel 42CrMo on the market, the relative corrosion rate of the 3.5%wt NaCl solution circulatory immersion test is ≤33%, the corrosion resistance is more than 3 times that of 42CrMo, the notch sensitivity NSR value is ≥1.65, the delayed fracture strength ratio is ≥0.80, the bolt has a high fatigue life, and the number of axial fatigue cycles under a load of 200KN is >2 million times.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] 1. The steel of the present invention adds Tb to modify the inclusions in the steel, reacting with oxygen and sulfur in the steel to generate high-melting-point spherical rare earth sulfides and rare earth oxysulfides randomly distributed in the crystal, replacing the Al2O3 inclusions and sulfide inclusions with greater hazards in the experimental steel, while promoting the dispersion distribution of fine spherical inclusions and improving the purity of molten steel. The steel of the present invention also controls the A value ≥ 1.25, A = (% Tb) / ((% S) + (% O)), ensuring that all inclusions are fully plasticized and the size is below 8.0 μm, thereby improving the comprehensive performance of the steel and the service life of the bolts.

[0041] 2. The present invention reduces the content of precious metals Ni and Cu in traditional Cr-Ni-Cu corrosion-resistant steel by adding Tb element, thereby effectively saving alloy cost.

[0042] 3. In the present invention, the chemical composition ratio is controlled to satisfy C value ≥ 7.38, C = 1.55 (% Si) + 3.97 (% Ni) + 1.85 (% Cr) + 2.03 (% Mo) + 6.42 (% P) - 7.23 (% Ni) (% P) + 69.72 (% Tb). Through the composite action of various corrosion-resistant elements, they precipitate at the interface between the rust layer and the substrate to form a barrier layer firmly bonded to the substrate, thereby blocking further dissolution of the substrate and promoting the formation of an amorphous FeOOH protective film.

[0043] 4. In the present invention, a bolt steel having a metallographic structure of pearlite + ferrite + a small amount of bainite and a bainite content of less than 10% is produced through a suitable process route. After quenching and tempering heat treatment, the strength of the bolt steel can reach 13.9 to 14.9, and the steel has excellent delayed fracture resistance, high room temperature impact toughness, and low temperature impact toughness. The corrosion resistance in the marine environment can be more than 3 times that of the high-strength bolt steel commonly used in the market, and the steel has low notch sensitivity, high delayed fracture resistance and high fatigue life, and is suitable for the production of ultra-high strength bolts for use in marine environments and other harsh open-air environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 is the metallographic structure diagram of the bolt steel in Example 1;

[0045] Figure 2 is the metallographic structure diagram of the bolt steel in Comparative Example 1;

[0046] Figure 3 This is a picture of the rust layer of the bolt steel in Example 2 after a 100-hour immersion test in a 3.5% wt NaCl solution;

[0047] Figure 4 This is a picture of the rust layer of the bolt steel in Comparative Example 4 after a 100-hour immersion test in a 3.5% wt NaCl solution. DETAILED DESCRIPTION

[0048] The invention provides a bolt steel, which contains, by weight percentage, C 0.40%-0.50%, Si 1.10%-1.30%, Mn 0.40%-0.60%, Alt 0.020%-0.030%, Mo 0.35%-0.45%, Cr 0.80%-1.00%, Ni 0.60%-0.80%, Tb 0.0050%-0.0080%, P≤0.015%, S≤0.015%, Cu≤0.10%, O≤0.0015%, H≤0.0002%, and the rest is Fe and other inevitable impurities;

[0049] Cl resistance - Corrosion index C value ≥ 7.38,

[0050] C=1.55(%Si)+3.97(%Ni)+1.85(%Cr)+2.03(%Mo)+6.42(%P)-7.23(%Ni)(%P)+69.

[0051] 72(%Tb);

[0052] A value ≥ 1.25, A=(%Tb) / ((%S)+(%O)).

[0053] The production method of bolt steel comprises the following steps: molten iron pretreatment→electric furnace or converter smelting→LF furnace refining→RH refining→square billet continuous casting→square billet heating→high-speed wire rolling→Stelmor cooling line cooling→Φ5.5-50mm wire rod finished product.

[0054] The electric furnace or converter smelting: the electric furnace or converter end point C≤0.04%, P≤0.006%; slag blocking for tapping, strict control of slag amount, slag layer thickness of the ladle≤100mm, tapping time≥5min.

[0055] The LF furnace refining: LF refining time is ≥30min, and white slag holding time is ≥20min, so as to ensure sufficient deoxidation, desulfurization and dephosphorization.

[0056] In the RH refining step, the RH vacuum control time is ≥20 min, and Tb blocks are added 10 min to 12 min before breaking the vacuum.

[0057] In the billet heating step, the soaking temperature of the heating furnace is controlled at 950°C to 1000°C.

[0058] In the high-speed wire rolling step, a controlled rolling and controlled cold rolling process is adopted, and the wire laying temperature is controlled at 830° C. to 860° C.;

[0059] In the cooling step of the Stelmore cooling line, the Stelmore line insulation cover is completely closed and the cooling rate is controlled below 0.13°C / s.

[0060] The present invention is described in detail below with reference to the embodiments.

[0061] The chemical composition and weight percentage of the bolt steel in each embodiment and comparative example are shown in Table 1.

[0062] Table 1

[0063]

[0064]

[0065] The production process route of the hot-rolled bolt steel wire rod in each embodiment and comparative example is: molten iron pretreatment → electric furnace or converter smelting → LF furnace refining → RH refining → billet continuous casting → billet heating → high-speed wire rolling → Stelmor cooling line cooling → Φ5.5~50mm wire rod finished product.

[0066] The production process parameters of the hot-rolled bolt steel wire rods in each embodiment and comparative example are shown in Table 2.

[0067] Table 2

[0068]

[0069]

[0070] A sample with a length of 15 mm was taken from the bolt steel wire rod in the embodiment and the comparative example, the cross section was polished, etched with 4% nitric acid alcohol, and the structure was evaluated according to GB / T 13298 "Methods for Examination of Metal Microstructures".

[0071] Inclusion size measurement: The inclusion size on the longitudinal surface of steel was measured and statistically calculated using an ASPEX scanning electron microscope.

[0072] Cold forging: The wire rod is cold forged according to the following requirements: X = h1 / h = 1 / 3, where: h is the height of the sample before cold forging (twice the wire rod diameter); h1 is the height of the sample after cold forging. After the cold forging test, the surface of the sample shall not have visible cracks, fissures, cracks and hairline defects. A group of 10 samples, all qualified are considered qualified.

[0073] The metallographic structure, inclusion size, and cold heading condition of the bolt steel wire rod in each embodiment and comparative example are shown in Table 3.

[0074] Table 3

[0075]

[0076]

[0077] The bolt steel wire rods in the above-mentioned embodiments and comparative examples were heat treated, and the specific heat treatment method was: first quenching at 900°C±10°C and then oil cooling, and then tempering at 570°C±20°C and then air cooling; or, first quenching at 900°C±10°C and then oil cooling, and then tempering at 530°C±20°C and then air cooling. The heat treatment parameters of the bolt steel wire rods in the embodiments and comparative examples are specifically shown in Table 4.

[0078] The bolt steel wire rods in the embodiments and comparative examples after heat treatment were subjected to tensile properties, KV2 impact test, notch sensitivity, delayed fracture resistance, and fatigue test tests. The specific test process is as follows:

[0079] Tensile properties: Refer to GB / T 228.1 "Metallic materials tensile test Part 1: Room temperature test method", process standard tensile specimens, conduct tensile tests, and test R m , A, Z values.

[0080] KV2 impact test: The specimens were processed into V-shaped impact specimens of 10mm×10mm×55mm, and GB / T229 “Charpy Pendulum Impact Test Method for Metallic Materials” was used to carry out 25℃ room temperature impact test and -80℃ impact test to obtain the impact toughness values, three values ​​were grouped together and the average value was calculated.

[0081] Notch sensitivity test: HB 5214-1996 "Method for notched tensile test of metals at room temperature" was used to conduct the notch sensitivity test. The notch sensitivity was measured by the ratio of the tensile strength of the notched specimen to the tensile strength of the unnotched specimen, i.e., the NSR value. The larger the NSR value, the lower the notch sensitivity. Since both the embodiment and the comparative example are plastic specimens and produce a notch strengthening effect, the NSR values ​​are all greater than 1. The NSR value of the embodiment is ≥1.65, which is significantly better than the comparative sample, has good notch sensitivity, and is suitable for making bolts.

[0082] Delayed fracture resistance test: Process the delayed fracture specimen, immerse the specimen in an acidic aqueous solution of 15% HCl for 30 minutes, wash and dry it, apply a certain load, and compare the load that does not break for more than 100 hours. At this time, the load that does not break for more than 100 hours after acid immersion is divided by the maximum load of the sample that is not acid-immersed during the tensile test, and the resulting value is defined as the delayed fracture strength ratio. A delayed fracture strength ratio of 0.70 or more is judged as qualified, and a ratio of 0.8 or more is judged as excellent. Through experiments, it was found that the delayed fracture strength ratios of the embodiments were all above 0.8, and all had excellent delayed fracture resistance.

[0083] Fatigue test: Axial fatigue test is carried out on MTS fatigue testing machine, using axial stress control, strain cycle characteristic of R=-1, controlled load of 200KN, frequency of 10Hz, 20 bolts as a group, and the test is considered successful when the number of cycles of 80% of the samples exceeds 2 million times.

[0084] Samples were taken from the square billets during the production of the bolt steel in each embodiment and comparative example, and quenched and tempered according to the parameters in Table 4, and then subjected to 100h salt solution environment Cl - The experimental process of ion corrosion immersion test is as follows: 3.5%wt sodium chloride solution is used to conduct the test according to the method of GB / T 19746 "Metal and Alloy Corrosion Salt Solution Immersion Test", complete the 72h immersion test, and calculate the corrosion weight loss rate, each number is 10 groups, and the average value is calculated. Compared with comparative example 4, which is the high-strength bolt steel 42CrMo commonly used on the market, the weight loss rate ratio of the test steel and the comparison steel is the relative corrosion rate of the test steel. The corrosion weight loss rate (W) is calculated as follows:

[0085]

[0086] Where: W——weight loss rate, g / (m 2 ·h); G0——original weight of the sample, g; G1——weight of the sample after the test, g; a——length of the sample, mm; b——width of the sample, mm; c——thickness of the sample, mm; t——test time, h.

[0087] The above test results are shown in Table 4.

[0088] Table 4

[0089]

[0090]

[0091] From the above content, it can be seen that the chemical composition and production method of the steel in Examples 1 to 8 are properly controlled, the hot-rolled wire rod is pearlite + ferrite + a small amount of bainite structure, one-third of the cold heading is qualified, the comprehensive strength and plasticity are high, and the user can simplify annealing when using it, reducing costs and pollution. In addition, the steel has high purity and high corrosion resistance, excellent delayed fracture resistance, high room temperature impact toughness, and low temperature impact toughness. The corrosion resistance in the marine environment can reach more than 3 times that of the 12.9 grade bolt steel commonly used in the market, and has low notch sensitivity, high delayed fracture resistance and high fatigue life, which is suitable for making ultra-high strength bolts used in marine environments and other harsh open-air environments.

[0092] Although the chemical composition of Comparative Example 1 is within the required range, the production method is not properly controlled. First, due to the late addition of Tb element, the plasticization of inclusions is not sufficient, and the maximum inclusion size in the steel reaches more than 9 μm, resulting in poor fatigue performance. In addition, improper rolling process control leads to the generation of a large amount of marbainite in the hot-rolled wire rod, and one-third of the cold heading is unsuitable. When users use it, they need to increase the annealing temperature and extend the annealing time, which increases costs and pollution; the corrosion resistance index C value in Comparative Example 2 is only 7.00 and does not reach 7.39, and the corrosion resistance is worse than that of the steel of the present invention; in Comparative Example 3, although the chemical composition of each element is not good, the corrosion resistance of the steel is poor. The content of the components is controlled according to the requirements of the present invention, but the purity A value does not reach 1.25, resulting in large inclusion size and low plasticity and toughness of the material. In addition, due to the presence of large inclusions, the fatigue life is low; Comparative Example 4 is a high-strength bolt steel 42CrMo commonly used in the market. Although the tempering temperature is controlled at a low level, its heat treatment strength can only reach level 12.9, and it does not have significant corrosion resistance, and its room temperature impact toughness and low temperature impact toughness are both lower than those of the steel of the present invention. In addition, since no plasticization treatment of inclusions is performed, the size of inclusions in the steel is large and the fatigue life is also low.

[0093] The detailed description of a bolt steel and its production method and heat treatment method with reference to the above embodiments is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. A steel for bolts, characterized in that: Contains by weight: C 0.40%~0.50%, Si 1.10%~1.30%, Mn 0.40%~0.60%, Alt 0.020%~0.030%, Mo 0.35%~0.45%, Cr 0.80%~1.00%, Ni 0.60%~0.80%, Tb 0.0050%~0.0080%, P≤0.015%, S≤0.015%, Cu≤0.10%, O≤0.0015%, H≤0.0002%, the rest is Fe and other inevitable impurities; Cl resistance - Corrosion index C value ≥ 7.38, C = 1.55 (% Si) + 3.97 (% Ni) + 1.85 (% Cr) + 2.03 (% Mo) + 6.42 (% P) - 7.23 (% Ni) (% P) + 69.72 (% Tb); A value ≥ 1.25, A=(%Tb) / ((%S)+(%O)); The metallographic structure of the bolt steel is pearlite + ferrite + a small amount of bainite, and the volume percentage of bainite is controlled below 10%; After quenching and tempering, the bolt steel has a KV2 impact toughness value of ≥200J at room temperature of 25°C, a KV2 impact toughness value of ≥90J at low temperature of -90°C, a relative corrosion rate of ≤33% in a 3.5%wt NaCl solution immersion test, a notch sensitivity NSR value of ≥1.65, a delayed fracture strength ratio of ≥0.80, and an axial fatigue cycle number of >2 million times under a load of 200KN.

2. The bolt steel according to claim 1, characterized in that: The bolt steel is oil-cooled after quenching at 890-910°C, and then air-cooled after tempering at 570°C±20°C. Its mechanical properties reach level 13.9, with Rm≥1300MPa, Rp0.2≥1170MPa, A≥8%, Z≥44%, and yield strength ratio≥0.

9.

3. The bolt steel according to claim 1, characterized in that: The bolt steel is oil-cooled after quenching at 900°C±10°C, and then air-cooled after tempering at 530°C±20°C. Its mechanical properties reach level 14.9, with Rm≥1400MPa, Rp0.2≥1260MPa, A≥8%, Z≥43%, and yield strength ratio≥0.

9.

4. The method for producing bolt steel according to any one of claims 1 to 3, characterized in that: The production method comprises the following steps: molten iron pretreatment → electric furnace or converter smelting → LF furnace refining → RH refining → billet continuous casting → billet heating → high-speed wire rolling → Stelmor cooling line cooling → Φ5.5~50mm wire rod finished product; In the RH refining step, the RH vacuum control time is ≥20 min, and Tb blocks are added 10 min to 12 min before breaking the vacuum; In the billet heating step, the soaking temperature of the heating furnace is controlled at 950° C. to 1000° C.; In the high-speed wire rolling step, a controlled rolling and controlled cold rolling process is adopted, and the wire drawing temperature is controlled at 830°C~860°C; in the Stelmor cooling line cooling step, the Stelmor line insulation cover is fully closed, and the cooling rate is controlled below 0.13°C / s.

5. The heat treatment method for bolt steel according to any one of claims 1 to 3, characterized in that: The heat treatment method comprises the following steps: first quenching at 900°C±10°C and then oil cooling, and then tempering at 570°C±20°C and then air cooling; or, first quenching at 900°C±10°C and then oil cooling, and then tempering at 530°C±20°C and then air cooling.

Citation Information

Patent Citations

  • Atmospheric corrosion resistant 08CrNiCu low-alloy high intensity non-annealed cold-forging steel and production process

    CN101397634B

  • Delay-fracture-resisting 1040 MPa-grade weather-proof bolt

    CN108070796A

  • 1400MPa grade delayed-breaking-resistant high-strength bolt steel and manufacturing method

    CN110423954A

  • Niobium-containing atmospheric-corrosion-resistant 14.9-grade high-strength steel for bolts and a production method thereof

    CN111041356A